1996
DOI: 10.1073/pnas.93.25.14776
|View full text |Cite
|
Sign up to set email alerts
|

A transgenic mouse model with an inducible skin blistering disease phenotype

Abstract: One of the current limitations of gene transfer protocols involving mammalian genomes is the lack of spatial and temporal control over the desired gene manipulation. Starting from a human keratin gene showing a complex regulation as a template, we identified regulatory sequences that confer inducible gene expression in a subpopulation of keratinocytes in stratified epithelia of adult transgenic mice. We used this cassette to produce transgenic mice with an inducible skin blistering phenotype mimicking a form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…Elucidation of the significance of K6 expression in wound healing or its function in the epithelia with constitutive expression would not only further our understanding of K6 but also potentially provide insight into the biological necessity of having different sets of keratins for different cell types. We have shown that expression of dominant-negative mutants of K6 in the companion cell layer leads to the destruction of these cells (47), and Takahashi and colleagues reported on inducible skin blistering after induction of a dominant-negative K6 transgene in the epidermis (42). However, the functional significance of a protein is sometimes better evaluated by analyzing the consequences of its absence.…”
mentioning
confidence: 99%
“…Elucidation of the significance of K6 expression in wound healing or its function in the epithelia with constitutive expression would not only further our understanding of K6 but also potentially provide insight into the biological necessity of having different sets of keratins for different cell types. We have shown that expression of dominant-negative mutants of K6 in the companion cell layer leads to the destruction of these cells (47), and Takahashi and colleagues reported on inducible skin blistering after induction of a dominant-negative K6 transgene in the epidermis (42). However, the functional significance of a protein is sometimes better evaluated by analyzing the consequences of its absence.…”
mentioning
confidence: 99%
“…The skin blistering disease epidermolytic hyperkeratosis has been induced in a transgenic mouse model by expression of phorbol ester-inducible regulatory sequences in a subpopulation of keratinocytes. Application of a phorbol ester produces induction of a mutant keratin product and the onset of disease (Takahashi and Coulombe, 1996). The ability to induce model diseases at will in this way should allow a better understanding of their aetiology and conse~ quently their treatment with the gene modification techniques described in this review (see Figure 3).…”
Section: Modeling Skin Disease Through Genetic Modificationmentioning
confidence: 99%
“…One role that has been ascribed to various keratin filament networks of stratified squamous epithelia is to impart mechanical integrity to cells, without which the cells become fragile and prone to rupture (2). Disruption of the keratin IF network in epidermal keratinocytes via the targeted expression of dominant negative keratin mutants (3)(4)(5) or the introduction of null mutations (6) results in lysis of the targeted cell population whenever the skin of such mice is subjected to trivial mechanical trauma. Mutations in keratin genes, weakening the structural framework of cells, increase the risk of cell rupture and cause various human skin disorders (7,8).…”
Section: Keratins Are Intermediate Filament (If) Composition Proteinsmentioning
confidence: 99%